2017
DOI: 10.1111/jcmm.13166
|View full text |Cite
|
Sign up to set email alerts
|

A novel pH‐controlled hydrogen sulfide donor protects gastric mucosa from aspirin‐induced injury

Abstract: Hydrogen sulphide (H2S) serves as a vital gastric mucosal defence under acid condition. Non‐steroidal anti‐inflammatory drugs (NSAIDs) are among widely prescribed medications with effects of antipyresis, analgesia and anti‐inflammation. However, their inappropriate use causes gastric lesions and endogenous H2S deficiency. In this work, we reported the roles of a novel pH‐controlled H2S donor (JK‐1) in NSAID‐related gastric lesions. We found that JK‐1 could release H2S under mild acidic pH and increase solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Recently, some controllable H 2 S donors have been developed. The representative examples are persulfide-based donors ( Zhao et al, 2013 ), N -mercapto-based donors ( Zhao et al, 2015 ), and JK type donors ( Kang et al, 2016 ; Yang et al, 2017a ), which are also shown in Figure 1 . These are considered “controllable” donors because their H 2 S release mechanisms are clearly exploited and the structural modifications could lead to H 2 S release profile changes (faster or slower).…”
Section: Donors Of Hydrogen Sulfidementioning
confidence: 99%
“…Recently, some controllable H 2 S donors have been developed. The representative examples are persulfide-based donors ( Zhao et al, 2013 ), N -mercapto-based donors ( Zhao et al, 2015 ), and JK type donors ( Kang et al, 2016 ; Yang et al, 2017a ), which are also shown in Figure 1 . These are considered “controllable” donors because their H 2 S release mechanisms are clearly exploited and the structural modifications could lead to H 2 S release profile changes (faster or slower).…”
Section: Donors Of Hydrogen Sulfidementioning
confidence: 99%
“…PCL-JK1 was found to significantly enhance the wound repair and regeneration efficiency compared with PCL fiber alone, likely due to the ability of H 2 S to inhibit inflammation, reduce oxidative damage and increase angiogenesis. In another example, Yang et al (2017) demonstrated that the intragastrical (IG) pre-administration of JK-1 protects gastric mucosa from aspirin (ASP)-induced gastric mucosal injury in vivo . Preconditioning with JK-1 alleviated ASP-induced inflammation response which was further validated by decreased levels of pro-inflammatory factors IL-6 and TNF-α.…”
Section: Ph-dependent Phosphonamidothioate-based Donors (Jk Donors)mentioning
confidence: 99%
“…Hydrogen sulfide (H 2 S) is an essential neuromodulator in mammals (Zheng et al, 2018), which regulates numerous pathophysiological functions in the digestive, respiratory, circulatory and nervous systems (Kimura et al, 2012;Drapala et al, 2017;Yang et al, 2017;Yu et al, 2017;Zhou et al, 2018). Endogenous H 2 S levels have been detected in the brains of rats and humans (Wang, 2012;Yang and He, 2019).…”
Section: Introductionmentioning
confidence: 99%